Corporate Governance and Earnings Management: Empirical Study of Public Companies in Indonesia - Mismiwati Mismiwati; Ravi Dara; Ming Kiri (Yayasan Adra Karima Hubbi, 2025)
Corporate governance plays a pivotal role in ensuring transparency and accountability in financial reporting, particularly in mitigating earnings management practices. Earnings management, which involves the manipulation of financial statements to present a desired image, undermines the reliability of financial information. In Indonesia, where corporate governance practices are still evolving, understanding the relationship between corporate governance and earnings management is critical for improving financial reporting quality. This study aims to examine the impact of corporate governance mechanisms on earnings management practices in public companies listed on the Indonesia Stock Exchange (IDX), providing insights into how governance structures can deter manipulative financial reporting. A quantitative research design was employed, utilizing data from 150 public companies listed on the IDX over a five-year period (2017-2021). Multiple regression analysis was used to analyze the relationship between corporate governance variables (e.g., board independence, audit committee effectiveness) and earnings management, measured using discretionary accruals. The findings reveal that stronger corporate governance mechanisms, particularly board independence and audit committee effectiveness, significantly reduce earnings management practices. Companies with higher governance scores reported lower levels of discretionary accruals, indicating more transparent financial reporting. This study highlights the importance of robust corporate governance in curbing earnings management.